MutT Homolog 1 Inhibitor Karonudib Attenuates Autoimmune Hepatitis by Inhibiting DNA Repair in Activated T Cells. Issue 5 (10th December 2021) - Chen, Yong; Hua, Xiangwei; Huang, Bingyuan; Karsten, Stella; You, Zhengrui; Li, Bo; Li, You; Li, Yikang; Liang, Jubo; Zhang, Jun; Wei, Yiran; Chen, Ruiling; et al.
Abstract : Autoimmune hepatitis (AIH) is an inflammatory liver disease driven by the hyperactivation of various intrahepatic antigen‐specific T cells due to a breach of immune tolerance. Studies in immunometabolism demonstrate that activated T cells harbor increased levels of reactive oxygen species that cause oxidative DNA damage. In this study, we assessed the potential of DNA damage repair enzyme MutT homolog 1 (MTH1) as a therapeutic target in AIH and karonudib as a novel drug for patients with AIH. We report herein that MTH1 expression was significantly increased in liver samples from patients with AIH compared to patients with chronic hepatitis B and nonalcoholic fatty liver disease and from healthy controls. In addition, the expression of MTH1 was positively correlated with AIH disease severity. We further found abundant T cells that expressed MTH1 in AIH. Next, we found that karonudib significantly altered T‐cell receptor signaling in human T cells and robustly inhibited proliferation of human T cells in vitro . Interestingly, our data reflected a preferential inhibition of DNA damage repair in activated T cells by karonudib. Moreover, MTH1 was required to develop liver inflammation and damage because specific deletion of MTH1 in T cells ameliorated liver injury in the concanavalin A (Con A)‐induced hepatitis model by inhibiting T‐cell activation and proliferation. Lastly, we validated the protective effect of karonudib on the Con A‐induced hepatitis model. Conclusion: MTH1 functions as a critical regulator in the development of AIH, and its inhibition in activated T cells reduces liver inflammation and damage.